Contra un enemigo infernal. Argumentos jesuíticos en defensa de la Amazonia hispánica : provincia de Maynas, 1721-1739 (2012)
ABSTRACT: With this article I will try to demonstrate how by the use of written arguments, some members of the Society of Jesus in the Real Audiencia de Quito were trying to counteract the projects of land occupation undertaken by the Portuguese Crown in the Northwestern of the Amazon basin (province of Maynas) during the 18th century. For that, I will use the different defensive arguments written by some of the jesuit missionaries against the Portuguese inhabitants from the capitanias of Grão Pará and Maranhão. Arguments that show the complexity of those imperial disputes, but that were not effective to prevent the constant military actions of the Portuguese armies that led to the loss of a huge jurisdictional fraction of the Spanish domains in South America.